1995
DOI: 10.1007/bf01271534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal melatonin on melatonin receptors in rat offspring

Abstract: Using quantitative autoradiography, we have studied the influence of maternal plasma melatonin on the expression and density of melatonin receptors in the brain and pituitary of rat offspring. At birth, the same structures displayed melatonin receptors whether the rats were born to and reared by intact or pinealectomized dams. The receptor density was, however, about 20% lower in the group born to pinealectomized dams. At postnatal day 9, when the pups of both groups synthetize rhythmically their own melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Notably, a nonsense mutation occurs in the MT2 coding gene in Siberian and Syrian hamsters, which disables the receptor . MEL-Rs are present in the pineal gland of the newborn rat, become rare in 9-day-old rats, and are not detected in adults (Zitouni et al, 1995). MEL-Rs have also been characterized in many peripheral structures such as the Harderian gland, spleen, testis, ovary, vascular system, gut, smooth muscle, and some cells of the immune system (see Vanecek, 1998 for review).…”
Section: Sites and Mechanisms Of Action Of Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a nonsense mutation occurs in the MT2 coding gene in Siberian and Syrian hamsters, which disables the receptor . MEL-Rs are present in the pineal gland of the newborn rat, become rare in 9-day-old rats, and are not detected in adults (Zitouni et al, 1995). MEL-Rs have also been characterized in many peripheral structures such as the Harderian gland, spleen, testis, ovary, vascular system, gut, smooth muscle, and some cells of the immune system (see Vanecek, 1998 for review).…”
Section: Sites and Mechanisms Of Action Of Melatoninmentioning
confidence: 99%
“…For example, in neonate but not adult rats, the pineal gland displays MEL-R binding (Zitouni et al, 1995). Exogenous MEL modifies various morphological and biochemical pineal parameters, namely proteic microtubules , enzymatic activities , presynaptic release of neurotransmitters , and pre and postsynaptic release of the MEL precursor serotonin (5-HT; Miguez et al, 1995b).…”
Section: Other Roles Of Melatoninmentioning
confidence: 99%
“…In the present study, film autoradiograms revealed specific I-MEL binding in discrete brain areas of near-term fetus and newborn mink: the olfactory epithelium, the cortex, the thalamus. All these areas were reported to show specific binding in neonate rodents with a large interspecies variation (rat: Zitouni et al 1995; Syrian hamster: Duncan and Davis 1993;Djungarian hamster: Weaver et al 1988;Carlsson et al 1991). The transient expression of specific I-MEL binding in the neonate mink brain corresponds to the decrease of binding sites during ontogenesis in the Syrian hamster (Duncan and Davis 1993) and the rat (Zitouni et al 1995).…”
Section: Discussionmentioning
confidence: 95%
“…In fact, in the rat, timed melatonin injections are able to entrain the circadian rhythm of N-acetyl transferase activity, the rate-limiting enzyme in melatonin synthesis (Humlova and Illnerova 1990); however, this effect is thought to be mediated by the SCN through melatonin receptors, which are lacking in mink. Furthermore, it is not known whether the pineal of the neonate mink can synthesize melatonin; in the rat, melatonin is present in the pineal by the end of the first week of life, in plasma from day 9, and a daynight difference is observed from day 10 ( Klein et al 1981;Zitouni et al 1995).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation